1972
DOI: 10.2337/diab.21.10.1013
|View full text |Cite
|
Sign up to set email alerts
|

Circulating C-peptide Immunoreactivity: Studies in Normals and Diabetic Patients

Abstract: The discovery of proinsulin and recognition of its intracellular conversion to insulin and C-peptide, which are stored and subsequently secreted together, have provided a simple method for monitoring β-cell function in insulinrequiring diabetics in whom insulin antibodies hinder measurement of immunoreactive insulin. Using an antiserum which reacts with antigenic determinants in human Cpeptide and this region in proinsulin and its intermediates we have measured C-peptide immunoreactivity (CPR) in unextracted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
6

Year Published

1974
1974
1983
1983

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(61 citation statements)
references
References 14 publications
2
51
6
Order By: Relevance
“…In 1972 Block et al [15], using C-peptide measurements, supported the view that Type 1 diabetes is characterized by a total deficiency of endogenous insulin secretion. Cpeptide was undetectable in newly diagnosed untreated Type 1 patients and in those who had received insulin for more than 5 years.…”
Section: C-peptide Measurements In the Assessment Of B Cell Functionmentioning
confidence: 66%
“…In 1972 Block et al [15], using C-peptide measurements, supported the view that Type 1 diabetes is characterized by a total deficiency of endogenous insulin secretion. Cpeptide was undetectable in newly diagnosed untreated Type 1 patients and in those who had received insulin for more than 5 years.…”
Section: C-peptide Measurements In the Assessment Of B Cell Functionmentioning
confidence: 66%
“…Recently the immunoassay system of human C-peptide of insulin has been developed by Melani et al (1970a), and Kaneko et al (1974), and many clinical results on the plasma or urine C-peptide immunoreactivity (CPR) have been reported in various diseases, especially in patients with [insulinoma or in insulin-treated diabetic subjects (Block et al, 1972(Block et al, , 1973Horwitz et al, 1975;Heding and Rasmussen, 1975;Kuzuya et al, 1977;Jaspan et al, 1977). The PLC contents of pancreas from diabetic and nondiabetic subjects were already studied (Rastogi et al, 1973;Hayashi et al, 1977), but the amount of C-peptide in human pancreas has not been reported.…”
Section: Synopsismentioning
confidence: 99%
“…Melani et al (Melani et al, 1970) have developed the radioimmunoassay using antiserum to albumin-conjugated natural human C-peptide. Although Rubenstein and his coworkers have demonstrated the presence of proinsulin and C-peptide in human serum using this assay system (Block et al, 1972(Block et al, ), 1972, it is extremely difficult to obtain suffrom natural source for immunization.…”
mentioning
confidence: 99%